Correction to: Treatment of Psoriasis with Secukinumab in Challenging Patient Scenarios: A Review of the Available Evidence - Jashin J. Wu; Joseph F. Merola; Steven R. Feldman; Alan Menter; Mark Lebwohl (Adis, Springer Healthcare, 2020)
The authors would like to correct the error in Table 1.